Analisis Just In Time (JIT) Persediaan Krudung di CV. Age Group - Maghfur Arafat; Muhammad Hermansyah (MES Bogor, 2024)
Every company always needs inventory, without having inventory, entrepreneurs will be faced with risks such as one time not being able to fulfill their customers' desires. This can happen, because goods are not always available at all times, which means entrepreneurs will lose the opportunity to gain the profits they should get. Therefore, the company must have an inventory management strategy in which the company must ensure that it is able to provide supplies with quality, quantity and time. Therefore CV. Age Groub must pay attention to storage capacity in order to meet demand for supplies of goods, and more attention must be paid to inventory management so that it remains well organized. By using the Just In Time approach. This research aims to optimize the efficient use of warehouse space to store goods with maximum capacity. The results using the Just In Time system approach are more efficient in calculating total inventory costs for the CV age group. The results obtained from analysis using the Just In Time method vary because they are based on various aspects. The greatest savings value is in the aspect of minimum inventory capacity from normal inventory with 66 deliveries which can save approximately 87% of the company's total costs, while from inventory which is added assuming damage, loss and defects of 5% with 73 deliveries can be achieved. save costs by 88%. So if you use the Just In Time system you will save costs of approximately 87-88%.